Conductive graphene coatings synthesized from graphenide solutions. (September 2017) - Wang, Yu; Huang, Kai; Derré, Alain; Puech, Pascal; Rouzière, Stéphan; Launois, Pascale; Castro, Celia; Monthioux, Marc; Pénicaud, Alain
Abstract: A simple preparation procedure to produce conductive graphene coatings from graphenide solution under inert atmosphere is achieved. The obtained graphene films exhibit reasonably low surface resistivity of 5 kohms/Square at 60% transmittance at 550 nm that can be largely improved by thermal treatment. XPS, Raman spectroscopy and X-ray diffraction measurements demonstrate that annealing vastly improves the quality of the graphene films. Heat treatment at low temperature (120 °C) demonstrates a 60% resistivity decrease, an impressive and promising improvement for films deposited onto flexible polymer substrate. Graphical abstract: